Pay Transparency Under Directive 2023/970 and Data Protection in EU Law - Kurzynoga, Małgorzata (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The aim of this article is to analyze the pay transparency measures introduced by Directive 2023/970 in the context of data protection law. Particular attention is given to the potential conflict between an employer’s obligations to report gender pay gaps and provide comparative salary data upon an employee’s request, and the obligations arising under data protection law. The data protection requirements established by the GDPR raise concerns regarding the potential reduction in the effectiveness of mechanisms designed to ensure pay transparency. At the same time, there are several arguments in favor of prioritizing pay transparency over data protection concerns.